Kant's moral theology: neither atheism nor vindication of the cause of God - Di Sanz, Silvia del Luján (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In this work we will maintain that, in Kant's critical work, the displacement of the idea of God from its traditional place of foundation, a displacement carried out by the three Critiques, relocates the function of the idea of God within his philosophy, and precisely for this reason, Kant considers that he has achieved that the shadow cast placed by dogmatic atheism on traditional metaphysics does not reach critical philosophy. So, the critical exercise of reason could be considered the antidote to atheism; however, at the same time, it has no effect in favor of the knowledge of divine designs. The displacement of the idea of God towards practical philosophy and its consequent location in moral theology makes it unfeasible or, we could also say unnecessary, for philosophy, to undertake the defense of the cause of God. None of this is without problems.